VD_FINDINFO Pron / 2013 / 32 vom 5. Februar 2013 - VD Tribunal cantonal (2013)
MOTIVATION DE LA DEMANDE, MOTIVATION DE LA DÉCISION, CONCLUSIONS, DÉCISION D'IRRECEVABILITÉ | 132 CPC (CH), 311 al. 1 CPC (CH)